Nutrition standards for the charitable food system: challenges and opportunities - Ronli Levi; Marlene Schwartz; Elizabeth Campbell; Katie Martin; Hilary Seligman (BMC, 2022)
Abstract Food insecurity is associated with increased risk of chronic disease and poor dietary intake. The United States charitable food system, a complex network of food banks, pantries and congregate meal sites, provides food for millions of low-income households each year. Food banks and pantries play a critical role in supporting food security and are an important contributor to dietary intake for its clients. In recent years, there has been an increased focus on sourcing and supplying more nutritious foods within the charitable food system. Despite this, there is a lack of alignment in how the charitable food system defines and tracks the nutritional quality of food. In 2019, Healthy Eating Research convened a panel of nutrition, charitable food system and food policy experts to create a set of evidence-based nutrition standards. Standards were developed based on a review of the literature and existing nutrition ranking systems, while also considering the operational needs and capacity of the charitable food system. The panel provided recommendations for eleven distinct food categories: fruits and vegetables, grains, protein, dairy, non-dairy alternatives, beverages, mixed dishes, processed and packaged snacks, desserts, condiments and cooking staples, and other miscellaneous items. Products are ranked into three tiers, choose often (green), choose sometimes (yellow) or choose rarely (red), based on designated saturated fat, sodium, and added sugar thresholds. This paper outlines the expert panel's approach and summarizes the barriers and opportunities for implementing these standards across the charitable food system.